Effect of Omega-3 fatty acids on blood pressure and serum lipids in continuous ambulatory peritoneal dialysis patients - Naini, Afsoon Emami (J Res Pharm Pract, 2015)
OBJECTIVE: Hypertension and hyperlipidemia are two major risk factors for cardiovascular disease in continuous ambulatory peritoneal dialysis (CAPD) patients. This study was designed to investigate the effect of omega-3 fatty acids on blood pressure (BP) and serum lipids in CAPD patients. METHODS: This study was a randomized double-blind clinical trial in which 90 CAPD patients were randomly assigned to either the omega-3 or the placebo group. Patients in omega-3 group received 3 g/day omega-3 for 8 weeks, whereas patients in the control group received placebo. At baseline and at the end of 8 weeks, the patients’ BP was controlled, and serum biochemistry was measured. FINDINGS: Mean systolic BP decreased (–22.2 ± 14.2 mmHg) in the omega-3 group at the end of the study while in the placebo group increased (+0.5 ± 30.2 mmHg) (P < 0.0001). Mean diastolic BP of the omega-3 group decreased more (–11.95 ± 11.9 mmHg) comparing with the placebo group (–1.1 ± 17.3 mmHg) (P = 0.001). There were no significant differences between the two groups in mean changes in serum triglyceride, and total, high-density lipoprotein, and low-density lipoprotein cholesterol. CONCLUSION: The results of this study indicate that omega-3 reduced BP significantly but had no effect on lipid profile in our CAPD patients.